Antinociceptive and anti-inflammatory effects of Lantana camara L. extract in mice - T.S.C. SILVA; I.B. SUFFREDINI; E.L. RICCI; S.R.C. FERNANDES; V.JR GONÇALVES; P ROMOFF; J.H.G LAGO; M.M. BERNARDI (Universidade Estadual Paulista, 2015)
ABSTRACT:he Lantana camara L. belongs to the family Verbenaceae, which contains several active compounds in leaves and roots and which are reported to have medicinal and insecticidal properties. Studies of plants within the same family show the existence of anti-inflammatory activity in paw edema induced by carrageenan, serotonin and histamine and analgesic activity in the acetic acid writhing and tail-flick tests. The present study investigated whether the L. camara extract (ACE) also exerts these effects. The ACE toxicity was studied in male mice, and the percentage of mortality recorded 7 days after treatment was assessed. The ACE was evaluated as an antinociceptive agent in the hot plate, tail-flick and acetic acid writhing tests at a nontoxic dose of 1.0 g/Kg. The results showed that 1.5 g/Kg of ACE was not able to cause death, and doses of 3.0 and 4.0 g/Kg caused 50% and 60% death, respectively, in male mice. In all of the antinociceptive tests, 1 g/Kg of ACE markedly reduced responses to pain. Our findings suggest that ACE may have active anti-inflammatory and antinociceptive properties in much smaller doses than toxic.